Acute Response of Toe-Spread-Out Exercise on Medial Longitudinal Arch Height and Balance - Jinseon Kim; Jusung Lee; Daeyoung Kim; Boymirzozoda Islomjon; Bobokyaw; Kichung Lee; Tejin Yoon (Asian Society of Kinesiology, 2021)
OBJECTIVES This study was to determine the acute response of the toe-spread-out exercise(TSE) on the medial longitudinal arch height(MLAH) and the static and dynamic balance. METHODS Twenty-four healthy young males and females were randomly assigned to the exercise group(n=12) or to the control group(n=12). The exercise group performed 40 repetitions of TSE while the control group had a rest on the chair. Before and after the exercise or rest, MLAH was measured while standing. One-leg standing test was conducted on the force plate with eyes closed and open. The total distance of the center of pressure (COP) was calculated to assess the static balance. Y-balance test was performed; and the anterior, and medial/lateral posterior reach distances were measured to assess the dynamic balance. RESULTS There was an interaction between group and time for the MLAH (p<.001), and the MLAH in the exercise group increased after the exercise (2.03±1.01 mm; t=-6.930, p<.001). There was an interaction between group and time for the anterior reach distance during the Y-balance test (p=.023), and the distance in the exercise group showed a strong tendency to increase after the exercise (t=-2.104, p=.059). No interaction was found for the total distance of the COP. CONCLUSIONS The 40 repetitions of TSE increased MLAH and showed a positive effect on dynamic balance in healthy young males and females. These results suggest that TSE can be useful as a new exercise method to improve the foot arch structure and function. Further research with the longer duration of TSE training for various populations is warranted.